Heart Failure with Preserved Ejection Fraction: A Case Report - Halimi, Amanda; Hersunarti, Nani (The Indonesian Heart Association, 2021)
Background: The prevalence of Heart Failure with Preserved Ejection Fraction (HFpEF) currently reaches 50% of heart failure cases and continues to increase every year. HFpEF is an important clinical condition, but the diagnosis is far more challenging than HFrEF (Heart Failure with Reduced Ejection Fraction), and there has not been any proven effective treatment. In this case presentation, the latest HFpEF diagnosis and therapy will be discussed. Case illustration and discussion: A man and a woman came to the emergency room with signs and symptoms of congestion suggestive of heart failure. Additional examination was performed to support the working diagnosis of HFpEF, namely ECG, NTproBNP and echocardiography. HFA-PEFF scores of the first and second patient was 3 and 4 respectively. During hospitalization, diuretics was given to overcome congestion according to guidelines, as well as ACE-inhibitor and beta-blocker. Both patients were also screened for cardiovascular and non-cardiovascular comorbidities, and were given appropriate therapy. Conclusion: The diagnosis of HFpEF does not have a gold standard yet, meanwhile, the HFA-PEFF scoring can be used. Recommended HFpEF therapy includes diuretics for congestion and management of comorbidities. Several studies of HFpEF treatment are ongoing.